Efficacy of platelet-rich plasma injection with percutaneous endoscopic lumbar discectomy for lumbar disc herniation: a systematic review and meta-analysis - Zhang, Yu; Ju, Jidong; Wu, Jinchun (Frontiers in Pharmacology, 2025)
ObjectiveOur aim was to compare the efficacy of percutaneous endoscopic lumbar discectomy (PELD) with or without platelet-rich plasma (PRP) injections for the treatment of lumbar disc herniation (LDH).MethodsLiterature was searched in six databases from inception to 2 May 2025. Meta-analysis was performed using stata17 software.ResultsEight studies were included, comprising a total of 717 patients (349 in the treatment group and 368 in the control group). At the final follow-up, the treatment group significantly provided lower visual analogue scale, intervertebral disc protrusion, recurrence rates, Oswestry disability index and higher intervertebral disc height, Japanese Orthopaedic Association scores, spinal canal cross-sectional area and ratio value of disc grey scale, compared to the control group (p < 0.05).ConclusionOur findings indicate that for the treatment of LDH, PELD combined with PRP injection markedly enhances clinical efficacy while reducing recurrence rates compared to PELD alone. Moving forward, larger multicenter randomized controlled trials with extended follow-up periods are necessary to confirm the long-term efficacy and safety of this combination therapy.Systematic Review RegistrationIdentifier CRD420251044871.